Deep-water, offshore, and new records of Schindler’s fishes, Schindleria (Teleostei, Gobiidae), from the Indo-west Pacific collected during the Dana-Expedition, 1928–1930 - Ahnelt, Harald; Sauberer, Michael (Zootaxa, 2020)
Schindleria (Giltay (1934), Schindler’s fishes (or infantfishes), is a genus of small (< 22 mm) paedomorphic species of the family Gobiidae which mature extremely fast. These fishes occur from the eastern Pacific (Cocos Islands off Costa Rica, seamounts Nazca and Sala y Gómez) to the southwestern Indian Ocean (southeast Africa). Nevertheless, there is a large gap in the distributional area between the Philippines (western Pacific) and India/Sri Lanka (Central Indian Ocean) which spans nearly 5000 km. We present the first comprehensive documentation of published records of Schindleria together with samples collected during the Dana-Expedition, between 1928 and 1930 at 44 stations from Polynesia to southeast Africa, with 8 records from the western Pacific to the Central Indian Ocean. We present three first records, 18 new records and the southernmost record for the Indian Ocean. Although Schindler’s fishes were generally documented from or close to islands and reefs, we present 23 offshore records (at least 30 km distant to a shore or reef) and 27 deep-water records (at least 65 m deep). Records between 320 and 360 km offshore are the most extreme offshore records of Schindleria ever documented. The records from about 500- and 1000-m depths are the deepest ever documented for Schindler’s fishes.